Rancang Bangun Aplikasi Omnichannel Untuk Customer Service Menggunakan Metode Decision Tree Sebagai Strategi Klasifikasi Kategori (Studi Kasus: Bisnis Naskine) - Lenida Nathania Ivana Sitorus; Dwi Fatrianto Suyatno (CV. SINAR HOWUHOWU, 2026)
Naskine customer service experiences difficulties in managing customer messages received through multiple communication channels, particularly WhatsApp and Instagram. The high volume of recurring customer inquiries and the limited capacity of admins to respond often result in delayed response times. This study aims to design and develop an omnichannel customer service application that integrates WhatsApp and Instagram into a single platform while automating the handling of frequently asked questions (FAQs). The Decision Tree method is applied to guide conversation flows based on predefined categories, enabling customers to obtain relevant information according to their needs. The application was developed using the Prototyping model with an iterative approach. The results indicate that the system improves the efficiency of customer service interactions through automated FAQ responses for recurring inquiries and structured message handling. The implementation of the system enhances response efficiency and allows admins to focus on conversations that require direct handling. The developed system can improve service quality and optimize customer service management.